Penguatan Kemandirian Ekonomi Desa Sumber Salam Kecamatan Tenggarang Bondowoso melalui Innovative Business Matching dengan Pendekatan Sustainable Livelihood Approach - Fajar Wahyu Prianto; Susanti Prasetiyaningtiyas; Dwi Perwitasari Wiryaningtyas; Moh. Adenan (INTEGRITAS : Jurnal Pengabdian, 2026)
The Village Development-Based Community Service Activity is proposed to be implemented in Sumber Salam Village, Tenggarang Subdistrict, Bondowoso Regency based on the following considerations: 1) Sumber Salam Village has been designated as an Independent Village but does not yet have its own income from the village's potential; 2) The performance achievement of SDGs in Sumber Salam Village is still low, namely 37.52 (scale of 100), particularly goal 8 (Equitable Village Economic Growth) and goal 9 (Partnerships for Village Development); 3) The village government is interested in developing a roadmap for revitalizing the village market and link and match as a priority for developing village economic independence. The objectives of this community service program are 1) Strengthening village economic independence and increasing Village Original Income (PADes) through a sustainable livelihood approach (SLA); 2) Developing local product markets using a market area model; 3) Economic resilience of the community based on link and match between local MSMEs and BUMDes with business associations, innovative business matching activities, and MSME clinics; and 4) Updating IDM and SDGs Village data, especially goals 8 and 17 related to village economic independence. The results of the 2025 community service activities are: (1) Roadmap for increasing PADes and strengthening village independence with a sustainable livelihood approach (SLA); (2) Roadmap for developing local product markets with a market area model; (3) Innovative business matching and coaching clinic activities that result in partnerships between local MSMEs and BUMDes with business associations (HIPMI and KADIN). The results of these activities were then published on the village website and in the mass media. In addition, they were also used as content in the local business database on the village website. The results of the activities are expected to update the data and improve the village's SDG achievements.